2012
DOI: 10.1080/13549839.2011.631990
|View full text |Cite
|
Sign up to set email alerts
|

Assessing urban sustainability from a social democratic perspective: a thematic approach

Abstract: Conventional typologies that seek to categorise indicators of urban sustainability tend to draw upon the neoliberal, silo approach for conceptualising sustainability, which positions sustainability as having economic, social and environmental dimensions. This approach has been critiqued for its inability to account for challenges to sustainability arising from interactions between social, economic and environmental variables. Models that are incapable of assessing dimensional interactions and their collective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
(39 reference statements)
1
28
0
Order By: Relevance
“…The literature points out that sustainability dimensions (i.e., three pillars plus additionally proposed dimensions) present a common framing for sustainability indicator selection [9,10,22]. Table 4 supports this claim, showing that 22 studies applied a three pillars framework and 26 organized around environmental and social sustainability.…”
Section: Sustainability Dimensions In the Literaturesupporting
confidence: 63%
See 2 more Smart Citations
“…The literature points out that sustainability dimensions (i.e., three pillars plus additionally proposed dimensions) present a common framing for sustainability indicator selection [9,10,22]. Table 4 supports this claim, showing that 22 studies applied a three pillars framework and 26 organized around environmental and social sustainability.…”
Section: Sustainability Dimensions In the Literaturesupporting
confidence: 63%
“…This was not a surprising finding, as the general literature on urban sustainability assessment acknowledges that this is the most typical approach [9,[21][22][23]. Although the indicator-based framework is the most common analytical tool, one should not necessarily blindly apply such an assessment protocol for future studies, as there are concerns in the literature that this approach is too often not grounded in clear sustainability principles and that indicators for urban sustainability assessment should be selected and organized through a more integrative perspective [6,10,24].…”
Section: Urban Sustainability Assessment Methods In the Literaturementioning
confidence: 76%
See 1 more Smart Citation
“…Equity has an intergenerational dimension, implying a concern with the distribution of resources available to current and future generations (Davidson, Kellett, Wilson, & Pullen, 2012). A social democratic approach to sustainability is necessarily predicated on an explicit set of values such as social justice, equity and environmental quality (Davidson, Kellett, Wilson, & Pullen, 2012, p. 63).…”
Section: Justice and Democracymentioning
confidence: 99%
“…The HCCF places a strong emphasis on the importance of social justice, equity, and natural capital. It seeks to better balance considerations of economic sustainability with social justice and equity, and sustainable environmental outcomes, while maintaining economic efficiency (Davidson, Kellett, Wilson, & Pullen, 2012). Huckle (2014) suggested that scholars could establish valid pathways to a common future along a broader direction that leads not only to sustainability but also to greater democracy and justice.…”
Section: Justice and Democracymentioning
confidence: 99%